2016
DOI: 10.1007/s00262-015-1790-5
|View full text |Cite
|
Sign up to set email alerts
|

The induction of human myeloid derived suppressor cells through hepatic stellate cells is dose-dependently inhibited by the tyrosine kinase inhibitors nilotinib, dasatinib and sorafenib, but not sunitinib

Abstract: Increased numbers of immunosuppressive myeloid derived suppressor cells (MDSCs) correlate with a poor prognosis in cancer patients. Tyrosine kinase inhibitors (TKIs) are used as standard therapy for the treatment of several neoplastic diseases. However, TKIs not only exert effects on the malignant cell clone itself but also affect immune cells. Here, we investigate the effect of TKIs on the induction of MDSCs that differentiate from mature human monocytes using a new in vitro model of MDSC induction through ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…11 MDSCs could be induced from mature human monocytes through HSCs dose-dependently. 35 Furthermore, activated human hepatic stellate cells induce myeloid-derived suppressor cells from peripheral blood monocytes in a CD44dependent fashion. 36 Bone marrow cells cultured with HSC-CM express lower levels of CD11c, CD80, CD86, and MHCII ( Figure 2B), suggesting that HSCs inhibit the differentiation of IMCs into mature myeloid cells and increase the expansion of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…11 MDSCs could be induced from mature human monocytes through HSCs dose-dependently. 35 Furthermore, activated human hepatic stellate cells induce myeloid-derived suppressor cells from peripheral blood monocytes in a CD44dependent fashion. 36 Bone marrow cells cultured with HSC-CM express lower levels of CD11c, CD80, CD86, and MHCII ( Figure 2B), suggesting that HSCs inhibit the differentiation of IMCs into mature myeloid cells and increase the expansion of MDSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Our data suggest that imatinib and nilotinib could decrease in vivo the half-life of circulating monocytes, as well as their recruitment and macrophage differentiation in tissues, possibly reducing the generation of macrophages that in the tumor microenvironment might acquire M2 tumor-promoting function. Interestingly, it has been shown that imatinib inhibited the early phase of the differentiation of myeloid-derived suppressor cells and reduced their number in CML patients (48), whereas it did not affect differentiation toward dendritic cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…88,95,96 Other MKIs (lenvatinib, regorafenib, and cabozantinib) have also demonstrated antitumor immune activity in various pre-clinical models. 78,79,81,97 While many of the immunomodulatory effects may be linked to the VEGFR-inhibitory property of these MKIs, multiple cellular and soluble factors in the tumour microenvironment may mediate their immunomodulatory effects (Fig. 1).…”
Section: The Importance Of Predictive Biomarkersmentioning
confidence: 99%